The Economic Ripple Effects of COVID-19 - Buera, Francisco J.; Fattal Jaef, Roberto N.; Neumeyer, P. Andres; Hopenhayn, Hugo; Shin, Yongseok (World Bank, Washington, DC, 2021)
What are the effects of a large temporary shock to the economy such as a temporary lockdown in response to a pandemic? Are the effects propagated and made persistent by firms’ deteriorating balance sheets and labor market frictions? This paper develops a model with financial market and labor market frictions to answer these questions. The model makes quantitative predictions about the effect on output, employment and firm dynamics from lockdowns of varying magnitude and duration. It finds that the effects are not persistent despite the deterioration of the financial soundness of non-essential firms and labor market frictions, if (i) laid-off workers can be recalled by their previous employers without having to go through the frictional labor market and (ii) the government provides employment subsidies to firms during lockdown. However, the effect are heterogeneous and young non-essential firms are disproportionately affected. In addition, if lockdowns lead to more permanent reallocation across industries, the recession becomes more protracted.